Pre-service teachers’ WhatsApp preferences in a mathematics methodology course during the COVID-19 pandemic - Sunzuma, Gladys; Zezekwa, Nicholas; Mutambara, Tendai L.; Chagwiza, Conilius; Gwizangwe, Isaac (DE Gruyter, 2022)
The study comprised thirteen pre-service teachers who were purposely sampled. Even though there are different online platforms that the pre-service teachers could have used, they all delivered their lessons through WhatsApp because of the several benefits attached to it such as ease and flexibility to use, low cost of WhatsApp bundles, various functions and the fact that it can be used anywhere at any time. The pre-service teachers faced several challenges during peer teaching using WhatsApp such as lack of smartphones, a flood of messages, human interruption, unavailability of electricity and internet and the nature of mathematics concepts. Difficulty in maintaining discipline, assessing learners’ progress was also difficult and it was time-consuming to prepare and deliver lessons using WhatsApp. The pre-service teachers suggested that the prices of online devices such as smartphones and WIFI should be subsidized. In addition, they suggested that lessons should be recorded for the learners and that parents should be involved in their children’s learning by encouraging them to provide online tools and educating them on online teaching and learning. The study recommends that pre-service teachers need to be trained on the use of online platforms so that they are equipped for any eventuality such as the COVID 19 pandemic.
Keywords: peer teaching; online learning; mathematics; pre-service teacher.